Brief Report: Real-World Efficacy and Safety of Sotorasib in U.S. Veterans with KRAS G12C-Mutated NSCLC - Katherine I. Zhou, MD, PhD; Chenyu Lin, MD; Chin-Lin Tseng, MPH; Nithya Ramnath, MBBS; Jonathan E. Dowell, MD; Michael J. Kelley, MD (JTO Clinical and Research Reports, 2024)
Introduction: The KRAS G12C inhibitor sotorasib was approved for treating advanced NSCLC in the second line or later on the basis of the CodeBreaK100 trial. Nevertheless, data on the real-world efficacy and safety of sotorasib, and to its optimal dose, remain limited. Methods: Patients treated with sotorasib for NSCLC through the Veterans Health Administration were retrospectively identified from the Corporate Data Warehouse. Survival, response, and toxicity data were obtained from chart review. Results: Among the 128 patients treated with sotorasib through the Veterans Health Administration, objective response rate was 34%, progression-free survival (PFS) six months, and overall survival 12 months. Similar PFS was observed among the 16 patients who received frontline sotorasib without any prior systemic therapy for NSCLC. Toxicity leading to sotorasib interruption or dose reduction occurred in 37% of patients, whereas sotorasib discontinuation for toxicity occurred in 25%. Notably, sotorasib dose reduction was associated with substantially improved PFS and OS. Conclusions: In this real-world study, the observed efficacy of sotorasib was similar to the results of CodeBreaK100. Patients who received frontline sotorasib had similar PFS to our overall cohort, suggesting that first-line sotorasib monotherapy may benefit patients who are not eligible for chemotherapy. Toxicities leading to sotorasib interruption, dose reduction, or discontinuation were common. Sotorasib dose reduction was associated with improved survival, suggesting that sotorasib dose reduction may not compromise efficacy.